Entrepreneurship and resilience: a systematic literature review - Souza, Amanda Priscila Bachiega Dadona; Nassif, Vânia Maria Jorge (Revista de Administração da UFSM, 2025)
Purpose: To identify characteristics of the resilient behavior of self-employed entrepreneurs in contexts of uncertainty. Design/methodology/approach: A Systematic Literature Review (SLR) was conducted based on the PRISMA-ScR protocol, using articles published between 2020 and 2025 from the Scopus and Web of Science databases. After applying filters, removing duplicates, and screening, 49 studies were qualitatively analyzed and organized into thematic clusters using Vosviewer software. Findings: Four dimensions of resilient behavior were identified: (1) intrapersonal resilience, related to emotions, attitudes, and beliefs; (2) strategies and proactiveness, associated with anticipating action and innovation; (3) coping with extreme adversities, such as the COVID-19 pandemic; and (4) connections, involving support networks and the use of technologies. The most recurrent characteristics include self-control, persistence, adaptability, positive attitude, faith, optimism, and seeking support, manifested in a combined and contextual manner. Research limitations/implications: Scarcity of studies dedicated exclusively to self-employed entrepreneurs, suggesting the need for further qualitative research. Practical implications: The findings can guide public policies and training programs that, in addition to technical skills, also foster socio-emotional and adaptive abilities. Social implications: By highlighting the importance of resilience, the study contributes to initiatives that support the sustainability of self-employed businesses, strengthening their economic and social role. Originality/value: Systematizes recent evidence on entrepreneurial resilience, detailing dimensions and strategies, and emphasizing the relevance of emotional and contextual aspects for survival and growth in uncertain environments.